2006
DOI: 10.1111/j.1469-7580.2006.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing impairment of secretory ameloblast function in porcine teeth by analysis of morphological alterations in dental enamel

Abstract: We studied the relationship between the macroscopic appearance of hypoplastic defects in the dental enamel of wild boar and domestic pigs, and microstructural enamel changes, at both the light and the scanning electron microscopic levels. Deviations from normal enamel microstructure were used to reconstruct the functional and related morphological changes of the secretory ameloblasts caused by the action of stress factors during amelogenesis. The deduced reaction pattern of the secretory ameloblasts can be gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(97 citation statements)
references
References 55 publications
5
92
0
Order By: Relevance
“…Instead, the trajectory of enamel growth reported here resembles the trajectory described for modern human and Neandertal deciduous molars, where a reduction in DSRs across the neonatal line was followed by a slow return to maximum rates of secretion (Macchiarelli et al, 2006). A reduction in the amount of secreted enamel matrix (inferred from a reduction in spacing between Retzius lines) has also been shown to correspond to a surface hypoplasia in wild boar and domestic pigs (Witzel, et al, 2006), while a recovery in enamel secretion after a systemic insult (increased fluoride) has been documented for roe and red deer (Kierdorf and Kierdorf, 1997). Like these studies, the M 1 in this study may also have retained a record of a systemic event that produced the reduction in enamel secretion in response to, for example, the type of juvenile illness that corresponds to some types of hypoplasia (e.g., Eliot et al, 1934;Pindborg, 1982).…”
Section: Daily Secretion Ratesmentioning
confidence: 76%
“…Instead, the trajectory of enamel growth reported here resembles the trajectory described for modern human and Neandertal deciduous molars, where a reduction in DSRs across the neonatal line was followed by a slow return to maximum rates of secretion (Macchiarelli et al, 2006). A reduction in the amount of secreted enamel matrix (inferred from a reduction in spacing between Retzius lines) has also been shown to correspond to a surface hypoplasia in wild boar and domestic pigs (Witzel, et al, 2006), while a recovery in enamel secretion after a systemic insult (increased fluoride) has been documented for roe and red deer (Kierdorf and Kierdorf, 1997). Like these studies, the M 1 in this study may also have retained a record of a systemic event that produced the reduction in enamel secretion in response to, for example, the type of juvenile illness that corresponds to some types of hypoplasia (e.g., Eliot et al, 1934;Pindborg, 1982).…”
Section: Daily Secretion Ratesmentioning
confidence: 76%
“…However, observations of strong enamel anomalies probably due to developmental defects recorded on two specimens ( Figure 10A & 10C) designated as Sus barbatus raise the distinct possibility of an early management of autochthonous bearded pigs. This idea has already been hinted at by recent phylogenetic evidence (Larson et al, 2007) and supported by the high frequency of dental enamel defects reported in European Neolithic Sus scrofa populations, compared with low frequencies in ancient and modern wild boar populations, purportedly a result of physiological stress due to the domestication process (Dobney et al, 2004;Witzel et al, 2006). Future studies of ISEA archaeological pig molars combining both geometric-morphometric approaches and systematic recording of enamel hypoplasia would be of great interest to investigate this question further.…”
Section: Molar Shape Divergence In Isea Wild Pigsmentioning
confidence: 80%
“…In this enamel zone, individual Retzius increments comprise a zone of aprismatic enamel external to a stria of Retzius and a zone of prismatic enamel further peripherally. This is regarded to reflect the fact that in late secretory ameloblasts, the recovery to full secretory activity and the concomitant re-establishment of a fully developed Tomes' process, required for the formation of prismatic enamel (Boyde, 1989;Kierdorf and Kierdorf, 1997;Witzel et al, 2006Witzel et al, , 2008, is delayed following the occurrence of a stria of Retzius. In our interpretation, the "minor striae" of Skinner and Pruetz (2012) constitute fracture faces formed at the transition between aprismatic enamel and prismatic enamel within a Retzius increment.…”
Section: Discussionmentioning
confidence: 99%